A Novel Transcription Complex That Selectively Modulates Apoptosis of Breast Cancer Cells through Regulation of FASTKD2 - Yeung, Kay T. (American Society for Microbiology, 2011)

(untitled)
We previously reported that expression of NRIF3 (nuclear receptor interacting factor-3) rapidly and selectively leads to apoptosis of breast cancer cells. DIF-1 (also known as interferon regulatory factor-2 binding protein 2 [IRF-2BP2]), the cellular target of NRIF3, was identified as a transcriptional repressor, and DIF-1 knockdown leads to apoptosis of breast cancer cells but not other cell types. Here, we identify IRF-2BP1 and EAP1 (enhanced at puberty 1) as important components of the DIF-1 complex mediating both complex stability and transcriptional repression. This interaction of DIF-1, IRF-2BP1, and EAP1 occurs through the conserved C4 zinc fingers of these proteins. Microarray studies were carried out in breast cancer cell lines engineered to conditionally and rapidly increase the levels of the death domain (DD1) region of NRIF3. The DIF-1 complex was found to repress FASTKD2, a putative proapoptotic gene, in breast cancer cells and to bind to the FASTKD2 gene by chromatin immunoprecipitation. FASTKD2 knockdown prevents apoptosis of breast cancer cells from NRIF3 expression or DIF-1 knockdown, while expression of FASTKD2 leads to apoptosis of both breast and nonbreast cancer cells. Thus, regulation of FASTKD2 by NRIF3 and the DIF-1 complex acts as a novel death switch that selectively modulates apoptosis in breast cancer.